Thai Buddhist Accounts of Male Homosexuality and AIDS in the 1980s - Jackson, Peter Anthony (The Australian journal of anthropology, 1995)
In this paper I consider the scriptural background to homophobic diatribes that emerged in the mid-1980s as the HIV epidemic slowly gained recognition in Thailand. By scrutiny of references to homosexuality in the Pali canon, I conclude that the scriptures are open to widely divergent interpretations. This doctrinal malleability is expressed in the contrasting views of contemporary Thai Buddhist intellectuals. The ‘traditional’ view claims that homosexuality is the kammic consequence of past sexual misconduct but in itself is not sinful and does not have future kammic consequences. The other, less tolerant view is that homosexuality derives from sexual excesses and, moreover, is the cause of the contemporary AIDS epidemic. Paradoxically it is the reformist Buddhist thinkers who have adopted the latter anti-homosexual position in that they tend to place less emphasis on kamma and more on individual responsibility for life circumstances.